The redefined role of two rivers in the making of Putrajaya Lake - Mohd. Yaman, Maheran; Nik Abdul Rahman, Nik Ismail Azlan (IIUM, 2009)
Abstract: Rivers along urban areas have recently begun receiving increased attention because of their valuable role in flood control or lack of it, providing water to support aquatic life and for visual impact. Another important but poorly understood function is water quality improvement. Rivers can actually provide effective, free treatment for many types of water pollution from point sources (municipal and certain industrial waste water effluents) and non-point sources (mine, agricultural and urban runoff) including organic matter, suspended solids, metals and excess nutrients. This paper will describe the process and will try to predict the effectiveness of the project.